Investigating the Impact of Stock Trading Volume, Market Capitalization, and Dividend Policy on Stock Returns: Challenges and Strategic Insights - Putri, Andini Amelia; Muliyani, Muliyani (Indonesian Financial Review, 2025)
This study examines the influence of trading volume, market capitalization, and dividend policy on stock returns of LQ45 companies listed on the Indonesia Stock Exchange from 2019 to 2023. Using a quantitative approach with purposive sampling and panel data regression analysis, the study analyzes 65 observations from 13 firms based on annual reports. The results indicate that all variables jointly affect stock returns. Partially, market capitalization has a significant positive effect, trading volume is not significant, and dividend policy has a significant negative effect. These findings suggest that stock returns in Indonesia are predominantly driven by firm fundamentals rather than market activity indicators. Trading activity may reflect short-term speculative behavior rather than fundamental value. By integrating signaling theory, market efficiency theory, and asset pricing theory, this study provides a comprehensive explanation of stock return determinants.